MERDEKA BELAJAR DALAM PERSPEKTIF ISLAM - Muhammad Erfan Muktasim Billah; Suwardi (Institute Agama Islam Al-Qolam Malang, 2021)
Education is the most important key in human life. Without education, in the formation of character, character and personality of a good person it is impossible to happen. The public has recently been shocked by the world of education, where the Minister of Education and Culture of the Republic of Indonesia, Nadiem Makarim, sparked the concept of independent learning. The concept of independent learning is an effort to deal with the changing times, where the goal is that students are given comfort in taking education, for example, the nuances of learning that are usually only in the classroom are now outside the classroom, so students can learn with the outside environment. In addition, they will not only listen to the teacher's explanation but can also shape the character of students who are more courageous, independent, and easy to get along with. Then what about Islam itself? Actually Islam from the beginning has given freedom in learning, this can be seen in the lives of the prophets, where they can learn under any conditions and are not limited by anything including time. This research uses secondary data sources to obtain relevant information from existing sources. The approach used in this research is qualitative using documentation, observation, and triangulation techniques